CERVICAL CANCER IS NOT A CHILDREN'S ILLNESS, ISN'T IT? - E.V. Uvarova; Z.Kh. Kumykova (Union of pediatricians of Russia, 2009)
The authors highlight the foreign authors review about the spread and peculiarities of the HPV infection and HPV'associated uterine cervix impairment in teenage girls. The interaction between HPV infection and uterine cervix impairment were described. There are also the most important prevention approaches in this issue. Key words: human papilloma virus, uterine cervix impairment, cervical cancer, screening, vaccination, teenage girls.